Cerpen “Kagami Jikoku” Karya Edogawa Rampo (Sebuah Kajian Struktural) - Yuliani Rahmah; Dwi Meinati (Diponegoro University, 2020)
The purpose of this research is to analyze the intrinsic elements found in the short story Kagami Jigoku by Edogawa Rampo. By using structural methods the analysis process find out the intrinsic elements which builds the Kagami Jikoku short story. As a result it is known that the Kagami Jikoku is a short story with a mystery theme as the hallmark of Rampo as its author. The characteristic of this short story can be seen from the theme which raised the unusual obsession problem of the main characters. With the first person point of view which tells in unusual way from the other short stories, the regression plot in Kagami Jikoku is able to tell the unique phenomenon of Japanese society and its modern technology through elements of place, time and socio-cultural aspects of Japanese society in the modern era